The Role of Health Worker in Performing Medical Services during Post Pandemic - Joseph Haddad (The Indonesian Journal of Community and Occupational Medicine, 2022)
Though have seems to reach the beginning of the end of the COVID-19 pandemic, there are still looming problems on the horizon. There are necessary adjustments needed with an end goal of supporting the ongoing COVID-19 response while at the same time strengthening our resilience and capacity to respond to public health emergencies in the future.The safety of health care workers (HCW) is an utmost priority and needs to be sustained; WHO has continuously called on governments and health care leaders to address the persistent threats to the health and safety of health workers and patients since the beginning of the pandemic. “The COVID-19 pandemic has reminded all of us of the vital role health workers play to relieve suffering and save lives,” said Dr Tedros Adhanom Ghebreyesus, WHO Director-General. “No country, hospital or clinic can keep its patients safe unless it keeps its health workers safe and ensuring that health workers have the safe working conditions, the training, the pay and the respect they deserve."1The pandemic has also highlighted the extent to which protecting health workers is key to ensuring a functioning health system and society. There are five critical mandatory actions to better protect health workers. These include protecting health workers from violence, improving their mental health, protecting them from physical and biological hazards, advancing national health worker safety programmes, and connecting health worker safety policies to existing patient safety policies.COVID-19 has exposed health workers and their families to unprecedented levels of risk. Although not representative, data from many countries across WHO regions indicate that COVID-19 infections among health workers are far greater than those in the general population. While health workers represent less than 3% of the population in most countries and less than 2% in nearly all low- and middle-income countries, around 14% of COVID-19 cases reported to WHO are among health workers. In some countries, the proportion can be as high as 35%. However, data availability and quality are limited, and it is impossible to establish whether health workers were infected in the workplace or their community.2 Regardless, thousands of health workers infected with COVID-19 have lost their lives worldwide.In addition to physical risks, the pandemic has placed extraordinary levels of psychological stress on health workers, who are exposed to highly demanding settings for long hours, constantly fearing disease exposure while separated from family and facing social stigmatization. Before COVID-19 hit, medical professionals were already at higher risk of suicide in all parts of the world. A recent review of health care professionals found that one in four reported depression and anxiety, and one in three suffered insomnia during COVID-19. WHO recently highlighted an alarming rise in reports of verbal harassment, discrimination and physical violence among health workers in the wake of COVID-19.3At the same time, it should be noted that the role and responsibilities of HCW are still the same before, during, and after the pandemic. Responsibilities of Health Care Workers involve a range of efforts relating to the diagnosis, response, and treatment of COVID-19 and supporting solutions to bring an end to this crisis, especially in maintaining the ongoing vaccination campaign.4,5 As the frontline in this fight against the pandemic, it is wise to involve HCW and their opinions in developing new treatments, vaccines and accurate diagnostic tests, streamlining processes where needed and appropriate, without compromising the scientific validity and reliability of proper research conduct. The involvement of HCW in the aforementioned process would ensure that treatments for patients would be realistic and practical in an actual clinical setting. It would be helpful to involve HCW in assuring adequate supplies of essential medical equipment such as ventilators. HCW has a vital role in this area because of the ability to identify and track patients who take illegitimate or black-market drugs. With widespread fear, anxiety, and panic surrounding the pandemic, there are countless snake oil salesman and quacksalver promising quick remedies to COVID-19 (and, without a doubt, any other subsequent pandemic in the future), which might pose more danger rather than benefits to the patients. HCW has the power to inform patients about dangerous products and unscrupulous marketers who may be selling products with false or misleading claims.There should be no rest to avoid further misfortune in this pandemic. Challenges are still ahead, but we must move forward and proceed to a new normal.